Allele‐Specific Inhibition of Histone Demethylases. (14th March 2019) - Wagner, Shana; Waldman, Megan; Arora, Simran; Wang, Sinan; Scott, Valerie; Islam, Kabirul
Abstract: Histone demethylases play a critical role in mammalian gene expression by removing methyl groups from lysine residues in degree‐ and site‐specific manner. To specifically interrogate members and isoforms of this class of enzymes, we have developed demethylase variants with an expanded active site. The mutant enzymes are capable of performing lysine demethylation with wild‐type proficiency, but are sensitive to inhibition by cofactor‐competitive molecules embellished with a complementary steric "bump". The selected inhibitors show more than 20‐fold selectivity over the wild‐type demethylase, thus overcoming issues typical to pharmacological and genetic approaches. The mutant–inhibitor pairs are shown to act on a physiologically relevant full‐length substrate. By engineering a conserved amino acid to achieve member‐specific perturbation, this study provides a general approach for studying histone demethylases in diverse cellular processes. Abstract : Give me some space : Bulky residues in histone demethylase KDM4A are replaced with amino acids with smaller side chain. The extra space created in the active site can accommodate inhibitors with a steric "bump" resulting in member‐specific perturbation of the lysine demethylases (KDM) family.